Imposex Cases in Snails (Thais Spp.) in the West Coast of Peninsular Malaysia - Mohamat Yusuff, Ferdius @ Ferdaus (2006)
The objective of this research was to assess imposex cases in Thais spp. from the west coast of Peninsular Malaysia with respect of identification of imposex severity by using the vas deferens sequence (VDS) scheme and relative penis length (RPL), the relationship between imposex level and sex ratio of Thais spp. through statistical analysis and relationship between length of imposex organs (VDS and RPL) and length of shell size parameters (height, edge and aperture). The present study also observed the relationship between imposex cases and human activities in the sampling areas. Sampling activities were carried out at 27 sites from five states along the west coast of Peninsular Malaysia from November 2001 to April 2004. The sampling sites were chosen based on the occurrence of Thais spp. In the present study, four species of Thais were chosen and they were Thais gradata, Thais tuberosa, Thais hippocastanum and Thais bitubercularis. These snails are well distributed along the rocky shore of the west coast of Peninsular Malaysia. T. gradata was found as the most abundant species, followed by T. tuberosa, T. hippocastanum and T. bitubercularis. The presence and development of imposex were observed in four species of Thais collected from the 27 sites along the west coast of Peninsular Malaysia. Almost 100% of female snails showed imposex characters in various degrees. The observed imposex developments in this study included a pseudopenis and / or a vas deferens sequence (VDS) and could be classified as stage 1, 2, 3, 4, 5 and 6 according to the VDS classification scheme. Most of the imposex cases occurred at stage 2 (60%), followed by stage 1 (19%) then stage 4 (8 %). While the rest were stage 3, 5 and 6. The serious level of imposex that is stage 6 formed a penis and VDS size grew 100% similar with the size of male’s sexual organs. The highest relative penis length (RPL) recorded in this study was 84.62%. The sex ratio of affected populations was deviated from normal ratio. There was also a significant correlation showing the increment of RPL caused the decrease on female population. From Pearson’s correlation coefficient, negative correlation coefficients found between imposex severity (which represent as RPL) with percentages of female population in T. gradata (r = - 0.0485, p > 0.05), T. hippocastanum (r = - 0.6034, p > 0.05) and T. bitubercularis (r = – 0.0707, p > 0.05). Furthermore, there was no obvious relationship between length of imposex organs (penis and VDS) and length of shell size parameters (height, edge and aperture). The incidence of imposex and the degree of imposex development in individuals were higher in samples collected from marinas, ports and areas with high boating and shipping activities.